2015
DOI: 10.1007/s00253-014-6317-z
|View full text |Cite
|
Sign up to set email alerts
|

Surfactin from Bacillus subtilis displays an unexpected anti-Legionella activity

Abstract: A contaminant bacterial strain was found to exhibit an antagonistic activity against Legionella pneumophila, the causative agent of Legionnaires' disease. The bacterial strain was identified as a Bacillus subtilis and named B. subtilis AM1. PCR analysis revealed the presence of the sfp gene, involved in the biosynthesis of surfactin, a lipopeptide with versatile bioactive properties. The bioactive substances were extracted from AM1 cell-free supernatant with ethyl acetate and purified using reversed phase HPLC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
49
1
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(57 citation statements)
references
References 58 publications
4
49
1
1
Order By: Relevance
“…Mireles et al (2001) observed that surfactin (at 100 µg) could reduce biofilm formation on urinary catheters by Salmonella enterica . A reduction in biofilm biomass formation in the presence of surfactin (at 66 µg/mL) was also observed for Legionella pneumophila (Loiseau et al 2015). …”
Section: Discussionsupporting
confidence: 56%
“…Mireles et al (2001) observed that surfactin (at 100 µg) could reduce biofilm formation on urinary catheters by Salmonella enterica . A reduction in biofilm biomass formation in the presence of surfactin (at 66 µg/mL) was also observed for Legionella pneumophila (Loiseau et al 2015). …”
Section: Discussionsupporting
confidence: 56%
“…[26,106,107] Recently, ethyl acetate has been successfully used to recover LP produced by Pseudomonas [12,108] and Bacillus. [89] This organic solvent can be used to substantially reduce recovery expenses and minimize environmental hazards. [109] Identification, characterization and quantification of LP by various chromatographic and spectroscopic techniques There are many chromatographic techniques used to characterize and quantify molecules, including thin layer …”
Section: Isolation and Purification Of Lpmentioning
confidence: 99%
“…There is limited number of reports available regarding the chemical nature of diffusible molecules responsible for anti-Legionella activity. Surfactin (lipopeptide), a well-characterized biosurfactant acquired from Bacillus subtilis, was found active toward various Legionella species including the Lens strain (CIP 108286) (Loiseau et al, 2015). According to previous reports, L. pneumophila was found to be sensitive to a variety of membrane-active biomolecules (Berjeaud et al, 2016).…”
Section: Biological Molecules Showing Anti-legionella Activitymentioning
confidence: 99%
“…A reference strain L. pneumophila serogroup 1 Lens CIP 108286 (Cazalet et al, 2008) was used for anti-Legionella strain selection. Spot-on-lawn assay was used for strain selection described previously by Loiseau et al (2015). Various inhibition zones of different diameters were observed, and stain showing maximum diameter was identified as most potent L. pneumophila competitor.…”
Section: Selection Of Anti-legionella Compounds Producersmentioning
confidence: 99%